Unique characteristics of new complete blood count parameters, the Immature Platelet Fraction and the Immature Platelet Fraction Count, in dengue patients. - Ikkoh Yasuda (Public Library of Science (PLoS), 2021)
The advanced platelet parameters Immature Platelet Fraction and Immature Platelet Fraction Count have been implemented in clinical practice as measures of thrombopoietic activity, mainly in hematologic disorders that cause thrombocytopenia. The purpose of this observational study was to examine thrombopoiesis as reflected by these 2 new CBC parameters in patients infected with dengue. The study was conducted in infectious disease referral hospital in Metro Manila, the Philippines. We enrolled hospitalized patients at admission who were diagnosed with acute dengue or community acquired bacterial infection (CABI). Immature Platelet Fraction (IPF) and Immature Platelet Fraction Count were evaluated at admission and during hospitalization. A total of 606 patients were enrolled from May 1, 2017 to June 1, 2018. The participants consisted of 152 patients with dengue infection, 180 confirmed CABI, and 274 suspected CABI patients. At admission, the percent IPF (IPF%) of the patients with dengue was significantly higher than that of the confirmed CABI patients (median 3.7% versus 1.9%; p <0.001). In a time course evaluation, there was no significant difference of IPF% between the patients with dengue infection and the confirmed CABI patients in the febrile phase (median 1.9% versus 2.4%; p = 0.488), however, the IPF% of the patients with dengue infection increased to be significantly higher than that of the confirmed CABI patients in the critical phase (median 5.2% versus 2.2%; p <0.001). Our study elucidated the unique characteristics and time-course trends of IPF percent and number (IPF#) in the patients with dengue infection. IPF% and IPF# are potentially valuable parameters in dengue and further investigation is required for the optimal use in clinical practice.